2001
DOI: 10.1093/ije/30.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Body size at birth and blood pressure among children in developing countries

Abstract: Raised blood pressure among children in three samples from China, Central and South America is related to proportionate reduction in body size at birth, which results from reduced growth throughout gestation. The relation between fetal growth and blood pressure may be different in African populations. Proportionately reduced fetal growth is the prevalent pattern of fetal growth retardation in developing countries, and is associated with chronic undernutrition among women. Improvement in the nutrition and healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(64 citation statements)
references
References 31 publications
3
60
0
1
Order By: Relevance
“…Studies have shown that low birth weight is associated with elevated blood pressure in adults and children [22]. Increased stature of mothers, favourable changes in socioeconomic factors and other factors such as improved maternal nutrition can be related to increased blood pressure [21].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that low birth weight is associated with elevated blood pressure in adults and children [22]. Increased stature of mothers, favourable changes in socioeconomic factors and other factors such as improved maternal nutrition can be related to increased blood pressure [21].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that low birth weight increases risk of several chronic adult diseases, including cardiovascular diseases (Barker 1999;Rich-Edwards et al 1997), hypertension (Law et al 2001), renal failure (Lackland et al 2000), and type 2 diabetes (Forsen et al 2000;Rich-Edwards et al 1999).…”
mentioning
confidence: 99%
“…In Africa, small studies of children in South Africa (24), Zimbabwe (25), and Gambia (26) suggested an inverse relationship between birth weight and BP when current body size was included in the model. In one Nigerian study (27), no statistical association was noted, regardless of whether BMI was included as an independent variable. The largest published study thus far of black populations is from Jamaica (28), where 1610 children who were aged 6 to 16 were found to have an inverse relationship between birth size and BP when current size was controlled in the model.…”
Section: Racial Disparity In the Relationship Between Birth Weight Anmentioning
confidence: 93%